OPTIMIZING MARKETING OF MICRO, SMALL, AND MEDIUM ENTERPRISE PRODUCTS THROUGH DIGITAL MARKETING TRAINING AND VILLAGE TOURISM STRATEGIES - Marcellia Susan; Anny Nurbasari; Budi Oktavianus Yusan; Yudhi Trisandy; John Salmar Saragih; Cen Lu (RADJA PUBLIKA, 2026)
The great potential of village tourism and micro, small, and medium enterprises (MSMEs) has not been matched by effective marketing strategies or digital utilization. This community service aims to enhance MSME competitiveness and promote tourism through digital marketing training. The method involved workshops, interactive sessions, and technical mentoring for 30 participants, including MSME actors, village tourism managers, and local communities. Pre- and post-training questionnaires showed an increase in digital marketing understanding from an average score of 4.08 to 4.29, and in tourism marketing strategies from 4.04 to 4.37. These findings confirm digital marketing's effectiveness in market expansion and tourism development. However, limitations in infrastructure and digital literacy remain barriers. Further training, internet access improvement, and multi-sector collaboration are required for long-term impact.